PENGARUH PENGARUH BENTUK DAN KONFIGURASI ALUR SEKAT TERHADAP UNJUK KERJA MENARA PENDINGIN (COOLING TOWER) - Hamid Abdul; Karim Lailul; Jamroni Mohammad; Qiram Ikhwanul; Gatut Rubiono Rubiono (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
The cooling tower is mechanical equipment which used to decrease hot waste water. One of the factors that influence the performance is the filling components. This research is aimed to get the effect of buffle’s shape and configuration due to cooling tower performance. The cooling tower performance is described with range, heat transfer rate, and efficiency. The research is done by an experiment using laboratory scale cooling tower. The shape is varied as circle and triangle with 2-3 and 3-2 in a row configuration. The water flow rate is adjusted with 3 valve opening. Water temperature inlet is varied as 50, 60 and 70oC. The measurements are taken for inlet and outlet water and air temperature for 3 times measurements using K-type thermocouples. The result shows that buffle’s shape and configuration have an effect due to cooling tower performance. Keywords: cooling tower, performance, buffle’s shape, configuration